2014
DOI: 10.1097/igc.0000000000000212
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs Involved in Gynecological Cancer

Abstract: Long non-coding RNAs (lncRNAs) are defined as transcripts longer than 200 nucleotides with little or no protein-coding capacity. Previously, they were considered transcription byproducts without biological functions. Further studies have shown that lncRNAs are involved in multiple biological and pathological processes, including regulation of epigenetic, transcriptional, and posttranscriptional events. Long non-coding RNA expression patterns in various malignant tumors differ from those of benign tumors and no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(21 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…It should be noted that this study was limited by its retrospective nature; however, a large number of cases were examined along with long term survival data. Many studies have shown that lncRNA acts as an unfavorable prognostic factor in various human cancers [17,18,29]; thus, the clinical and prognostic significance of HOXA11as were identified in this study. Moreover, only serous type histology was investigated to overcome the heterogeneity of the study population.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It should be noted that this study was limited by its retrospective nature; however, a large number of cases were examined along with long term survival data. Many studies have shown that lncRNA acts as an unfavorable prognostic factor in various human cancers [17,18,29]; thus, the clinical and prognostic significance of HOXA11as were identified in this study. Moreover, only serous type histology was investigated to overcome the heterogeneity of the study population.…”
Section: Discussionmentioning
confidence: 94%
“…Several lncRNAs have been identified in gynecological cancer, including HOTAIR , MALAT-1 , H19 , and LSINCT5 [17]. One of the most popular oncogenic lncRNA studied is HOX transcript antisense intergenic RNA ( HOTAIR ), which our group recently identified as playing a role in cell proliferation and invasion in cervical cancer cell lines [18].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, its expression is induced by carboplatin, thus raising the sensitivity of ovarian cancer cells to this drug [121]. More studies are needed to elucidate its role in modulating sensitivity to cisplatin and its modes of regulation, which could lead to new ways of predicting and/or modulating the clinical response to this drug [122]. …”
Section: Lncrnas With a Role In Ovarian Cancermentioning
confidence: 99%
“…Ovarian cancer is a common gynecological malignant tumor, as well as one of the most lethal gynecological malignancies in the world . Despite improvements in surgery, radiotherapy and neoadjuvant chemotherapy as the main methods to treat ovarian cancer, the 5‐year survival rate of patients is still only 30% . The lack of biomarkers for early detection and diagnosis is the major cause of the low survival rate.…”
Section: Introductionmentioning
confidence: 99%